2021
DOI: 10.3390/en14154700
|View full text |Cite
|
Sign up to set email alerts
|

Energy Efficiency and Carbon Emission Impact on Competitiveness in the European Energy Intensive Industries

Abstract: Climate change and efforts to mitigate it have given rise to an interest in the relationship between industry competitiveness, energy efficiency, and carbon emissions. A better understanding of this relationship can be essential for economic and environmental decision-makers. This paper presents empirical research evaluating industry competitiveness through the factors of energy efficiency and carbon emission in Europe’s most energy-intensive industries. The designed industry competitiveness measure index cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 59 publications
1
0
0
Order By: Relevance
“…The total CO 2 emissions from cement manufacturing are estimated at 8% of the world total [87]. For the basic metals sector, our results are somewhat consistent with those of [88], who found that Portugal and Lithuania are among the most competitive countries in this industry from the perspective of energy, emissions, and export performance indicators, whereas Czechia and Ireland are among the least competitive. In our case, Portugal and Lithuania registered a high performance with a low ratio (5% and 1%, respectively), whereas Czechia and Ireland have a high ratio (50% and 38%, respectively).…”
Section: Resultssupporting
confidence: 88%
“…The total CO 2 emissions from cement manufacturing are estimated at 8% of the world total [87]. For the basic metals sector, our results are somewhat consistent with those of [88], who found that Portugal and Lithuania are among the most competitive countries in this industry from the perspective of energy, emissions, and export performance indicators, whereas Czechia and Ireland are among the least competitive. In our case, Portugal and Lithuania registered a high performance with a low ratio (5% and 1%, respectively), whereas Czechia and Ireland have a high ratio (50% and 38%, respectively).…”
Section: Resultssupporting
confidence: 88%